Preference Level Of Lauwon Soybean Coffee - Ramadhani Chaniago; Winarto Ramlan; Darni Lamusu (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2026)
Purpose: This study aimed to evaluate the composition and consumer preference level of Lauwon soybean coffee as an innovation in local soybean-based food diversification. The research is important to support the development of non-caffeinated alternative beverages based on plant protein and to increase the added value of soybeans through postharvest processing, while providing a scientific basis for the development of soybean coffee as a functional food product rooted in local wisdom. Methodology: The study was conducted in two phases: (i) production of soybean coffee by the community of Lauwon Village, Banggai Regency, involving sorting, washing, roasting, grinding, sieving, and packaging; and (ii) evaluation of consumer preference using a five-point Likert-scale organoleptic test. A total of 50 semi-trained panelists participated, assessing color, taste, aroma, and viscosity. The data were analyzed descriptively. Results: The results showed that soybean coffee had a dark brown color with a characteristic roasted aroma. Consumer preference scores were categorized as slightly liked/moderate for color and viscosity, and ranged from disliked to slightly liked/moderate for taste and aroma. Roasting was identified as the dominant factor influencing the sensory attributes. Findings: The findings indicate that Lauwon soybean coffee is moderately acceptable to consumers but requires process optimization to improve taste and aroma. Novelty: The novelty of this study lies in the utilization of local Lauwon soybeans as an analog coffee product and the direct evaluation of consumer preferences. Originality: Originality is demonstrated through the integration of community-based production processes with scientific sensory analysis. Conclusion: Lauwon soybean coffee has potential to be developed as an innovative alternative beverage based on local resources, with further optimization of the roasting process. Type of Paper : Research Article.